Effects of Blended Learning in Teaching Mathematics in Higher Education - POKORNÝ, P.; HÍC, Pavel (Journal of Education, Technology and Computer Science, 2015)
Blended learning represents a combination of online learning and face-toface instruction. While one group of researchers advocates the use of blended learning in teaching, others are more critical to the use of ICT in education. The paper deals with utilization of blended learning in teaching mathematics at Faculty of Education, Trnava University. From the results it follows that proper integration of ICT into teaching can make the teaching process more efficient.